Associations between adverse childhood experiences and trust in health and other information from public services, professionals and wider sources: national cross sectional survey - Mark A Bellis; Karen Hughes; Kat Ford; Catherine Sharp; Rebecca Hill (BMJ Public Health)
Introduction Trust in health and other systems can affect uptake of public health advice and engagement with health services. Individuals who had adverse childhood experiences (ACEs) are more likely to experience ill health at earlier ages. Ensuring their engagement with health and other services is important in improving their life course prospects, but little is known about how ACEs affect trust in such services and the information they provide.Methods Data were collected via a national household survey of residents in Wales (aged ≥18 years, n=1880, November 2022–March 2023). Questions measured ACE exposure and trust in health, social, police, charities and government, and health and general information provided by a variety of professionals and sources.Results Individuals with ACEs were more likely to report low trust in health advice from hospital doctors, general practitioners (GPs), nurses, pharmacists, and NHS 111, an online and telephone urgent care service (eg, adjusted low trust prevalence: GPs, 0 ACEs 5.3%, ≥4 ACEs 10.4%; NHS 111, 0 ACEs 11.9%, ≥4 ACEs 24.1%). Low trust in services also increased with ACEs, with low trust in police being 3.8 times more likely with ≥4 ACEs (vs 0 ACEs). The highest adjusted prevalence of low trust in a service was for government, rising from 48.4% (0 ACEs) to 73.7% (≥4 ACEs). Low trust in general advice and information from TV/radio programmes rose from 17.6% (0 ACEs) to 30.1% (≥4 ACEs); low trust in social media was higher with an equivalent rise from 61.6% to 75.6%.Conclusion Breaking intergenerational cycles of ill health and inequity requires engaging and influencing those with ACEs. However, a history of ACEs was associated with lower trust in supporting institutions, systems and professionals. Empirical data on which resources are most trusted by those with ACEs should be used to facilitate better communications with this vulnerable group.